Answer:
B IS THE ANSWER
Step-by-step explanat
(22x2 - 8x) - 12 = 0
4x2 - 8x - 12 = 4 • (x2 - 2x - 3)
The first term is, x2 its coefficient is 1 .
The middle term is, -2x its coefficient is -2 .
The last term, "the constant", is -3
Step-1 : Multiply the coefficient of the first term by the constant 1 • -3 = -3
Step-2 : Find two factors of -3 whose sum equals the coefficient of the middle term, which is -2 .
-3 + 1 = -2 That's it
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -3 and 1
x2 - 3x + 1x - 3
Step-4 : Add up the first 2 terms, pulling out like factors :
x • (x-3)
Add up the last 2 terms, pulling out common factors :
1 • (x-3)
Step-5 : Add up the four terms of step 4 :
(x+1) • (x-3)
Which is the desired factorization
4 • (x + 1) • (x - 3) = 0
A product of several terms equals zero.
When a product of two or more terms equals zero, then at least one of the terms must be zero.
We shall now solve each term = 0 separately
Any solution of term = 0 solves product = 0 as well.
Solve : x+1 = 0
Subtract 1 from both sides of the equation :
x = -1
Solve : x-3 = 0
Add 3 to both sides of the equation :
x = 3